Protective effect of (-)-epigallocatechin-3-gallate against cisplatin-induced ototoxicity. Issue 4 (April 2014) - Cho, S I; Lee, J H; Park, J H; Do, N Y
Abstract Objective: Ototoxicity due to cisplatin therapy interferes with treatment and often forces a reduction in the dosage, duration and frequency of the cisplatin therapy. (-)-Epigallocatechin-3-gallate is known to have the highest antioxidant potency among all tea catechins. This study aimed to investigate the effect of (-)-epigallocatechin-3-gallate on cisplatin ototoxicity in an auditory cell line: House Ear Institute-Organ of Corti 1 cells. Methods: Cultured House Ear Institute-Organ of Corti 1 cells were exposed to cisplatin with or without pre-treatment with (-)-epigallocatechin-3-gallate. Cell viability was evaluated using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. Hoechst 33258 staining was used to identify cells undergoing apoptosis. Western blot analysis was conducted to determine whether (-)-epigallocatechin-3-gallate inhibited cisplatin-induced caspase activation. Intracellular reactive oxygen species production was examined to investigate whether (-)-epigallocatechin-3-gallate was capable of scavenging cisplatin-induced reactive oxygen species accumulation. Results: Cell viability significantly increased in cells pre-treated with (-)-epigallocatechin-3-gallate compared with cells exposed to cisplatin alone. Cisplatin increased cleaved caspase-3 on Western blot analysis; however, pre-treatment with (-)-epigallocatechin-3-gallate inhibited the expression of caspase-3. (-)-Epigallocatechin-3-gallate attenuated reactive oxygen species production and apoptosis in House Ear Institute-Organ of Corti 1 cells. Conclusion: (-)-Epigallocatechin-3-gallate protected against cisplatin cytotoxicity through anti-apoptotic and anti-oxidative effects. Therefore, (-)-epigallocatechin-3-gallate could play a preventive role in cisplatin-induced ototoxicity.